2018
DOI: 10.1159/000486461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Videodermoscopic Evaluation of the Efficacy, Safety, and Tolerability of a Shampoo Containing Ichthyol, Zanthalene, Mandelic Acid, and Honey in the Treatment of Scalp Psoriasis

Abstract: Purpose of the Study: The aim of the present prospective multicenter open study was to clinically and instrumentally evaluate the efficacy, safety, and tolerability of a shampoo, Mellis Cap® shampoo, containing ichthyol, zanthalene, mandelic acid, and honeydew honey in the treatment of mild to moderate scalp psoriasis. Procedures: Thirty subjects with mild to moderate psoriasis applied the shampoo three times a week for 12 weeks. The outcome was evaluated at 30 days (T1), 60 days (T2), and 90 days (T3) of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…11 This study concluded that a honeydew honey shampoo mixture is a proven alternative to medicated shampoos for mild-to-moderate scalp psoriasis. 11 Lastly, a double-blind, placebo-controlled randomized clinical trial of participants with moderateto-severe psoriasis that explored the safety and efficacy of oral curcumin when used concomitantly with phototherapy established that curcumin was well tolerated and demonstrated a positive response as an adjunct to phototherapy, as 80% of subjects in both groups achieved a 90% decrease in PASI scores by the study conclusion. 30…”
Section: Qualitative Results Stratified By Diseasementioning
confidence: 84%
See 4 more Smart Citations
“…11 This study concluded that a honeydew honey shampoo mixture is a proven alternative to medicated shampoos for mild-to-moderate scalp psoriasis. 11 Lastly, a double-blind, placebo-controlled randomized clinical trial of participants with moderateto-severe psoriasis that explored the safety and efficacy of oral curcumin when used concomitantly with phototherapy established that curcumin was well tolerated and demonstrated a positive response as an adjunct to phototherapy, as 80% of subjects in both groups achieved a 90% decrease in PASI scores by the study conclusion. 30…”
Section: Qualitative Results Stratified By Diseasementioning
confidence: 84%
“…In patients with mild-to-moderate scalp psoriasis, a prospective multicenter study examining treatment with honeydew honey added to a shampoo mixture showed improvement of clinical and patient-reported parameters. 11 This study concluded that a honeydew honey shampoo mixture is a proven alternative to medicated shampoos for mild-to-moderate scalp psoriasis. 11 …”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations